Trade Policy and WTO Accession for Economic Development : Application to Russia and the CIS, Module 11. Antidumping and Other Measures of Contingent Protection - Navaretti, Giorgio Barba (World Bank, Washington, DC, 2017)
This report summarizes the measures of contingent protection regulated by the WTO and their purposes. They can be divided into two categories. The first one regards temporary provisions that can be used when a predefined set of circumstances legitimize temporary increases in import barriers. The second one includes permanent exceptions to the general obligations. Temporary restrictions allowed by the WTO are anti-dumping duties, countervailing duties, and safeguard measures, (tariffs to assist with balance of payments problems, tariffs to protect infant industries, or tariffs for emergency protection). Permanent exceptions are general waivers from binding obligations, which, in contrast with the other mechanisms, must be formally approved by the WTO Council.